IMPLEMENTATION OF FIELD STUDIES TO IMPROVE PROBLEM ANALYSIS ABILITY (CASE STUDY IN THE STUDENT SOCIOLOGY IISIP YAPIS BIAK) - Ahmad, Busyairi; Laha, M. Saleh (Lembaga Penelitian Mahasiswa Penalaran UNM, 2020)
The study aims to analyse the impact of the implementation of field studies in enhancing the problem-analysis skills and problem solving problems of sociology students in IISIP Yapis Biak. This research uses a qualitative approach. Data collection is done by interview, observation, and documentation methods. The data are analyzed by using data reduction, data feed and conclusion withdrawal. The results showed that the implementation of field studies in lecturing was able to provide students with the ability to analyse problems and even solve problems. The evidence showed when students did assegnment to observe a problem in order to be analyzed and solved and the result showed they did with a good solving. Therefore, the students did not only accept the theory but also be able to apply it to the real situationals.